VO#043 Quotation for components material cost in internal electrification works rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of quotation for components material cost in internal electrification works of BRACU new campus project.